RNase Y mediates posttranscriptional control of the virulence-associated CncR1 small-RNA in Helicobacter pylori - Federico D’Agostino; Eva Pinatel; Alexandra Meynhardt; Vincenzo Scarlato; Andrea Vannini; Davide Roncarati (iScience)
Summary: Ribonucleases are involved in several biological processes, including the turnover of structural and messenger RNAs and the specific processing of the cellular transcriptome. Here, we characterized the RNase Y from Helicobacter pylori. We found that RNase Y is membrane-associated and its expression is controlled during bacterial growth and by Fur in response to iron. We observed that RNase Y deletion has a limited impact on H. pylori transcriptome and on bacterial growth. Interestingly, we found that RNase Y is involved in the metabolism of CncR1, a virulence-associated sRNA oppositely modulating bacterial motility and adhesion to host cells. Indeed, RNase Y inactivation led to the accumulation of a 3′-extended CncR1 isoform, which appeared unable to interact in vitro with a known target mRNA. The observation that the RNAse Y-mutant strain showed deregulation of several members of the CncR1 regulon suggests this ribonuclease has an important role in H. pylori posttranscriptional regulation.